A method for selecting agricultural land from production and conversion forests in Indonesia - Ross, M (Commenwealth Forestry Institute, University of Oxford, 1983)
Indonesia needs more agricultural land to feed its growing population. Presently 60% of the surface is covered with forest of which 25% of the land has already been allocated as conservation and watershed protection forests. Approximately 93 million hectares of additional forest on slopes less than 30% are classified as production and conversion forests, the former assigned for the sustained production of industrial logs whilst the latter may be converted to agriculture. Thirty million hectares of this are presently classified as Conversion Forest. In the Fourth Five Year Development Plan, Repe1ita IV, at least 12 million hectares of Production and Conversion forests will be required to be converted to agricultural settlements for transmigrants. It would appear that the 12 million hectares could easily be selected from the 30 million hectares of Conversion Forest. This is not so, for Government policy demands that the settlers are self sufficient in food. In general, sustained food cropping without environmental deterioration requires relatively flat ground. In. practice, this means that planners are instructed in their TOR to include one out of 3.5 hectares per family of land on slopes less than 8%. This is to be.used for the production of dryland rainfed arable crops or, if suitable, wetland rice production. Unfortunately, the topography makes this requirement very difficult to satisfy. Thus transmigration planners sometimes have to look inside the Production Forest area for land satisfying the slope requirements. Because of sectoral interests, an objective and scientific method is':required to select such land, taking into consideration both sustained forestry aspects and agricultural requirements. The paper suggests a method of classifying Moist Tropical Forests according to their ability to yield industrial logs. Five factors are taken into account in classifying these forests into nine classes, three are highly suitable, three are moderately suitable, two are of low suitability and those which are not suitable. The factors are: volume of standing stock above 70 cm dbh, potential for regeneration, type of species, access within a particular area and location. Next, a methodology was prepared on how to decide if a piece of land should be converted to agriculture. The main points of the Methodology concern: forestry suitability compared with agricultural suitability for food crops, the minimum forest estate for the production of industrial wood, the need for the forest estate to be well distributed, the forest management system, the possibility to utilize wood made available as a result of land clearing, the minimum size of forest concessions, the location of forests in relation to the industries being supplied logs, the proposed method of transportation of these logs, the comparative economics of agriculture versus forestry, the legal status with regard to a particular areas availability to change its use and conservation issues. Seven areas examined for their suitability for Transmigration in 1982 have been tested both for their suitability for forestry by the introduced method and by the FAO method for agriculture. The suitabilities were then compared according- to the 'Methodology' and conclusions drawn as to the best use of the land. As all the areas have been put to transmigration, the results show that in some cases areas should have been left as forests and alternate areas tested for their suitability for agriculture.